Inovasi Pendekatan Sistem Pembelajaran Dalam Pendidikan Agama Islam: Strategi Pembentukan Karakter di Era Digital di Madrasah - Dea Ayunda; Dhea Puspita; Lutfiah Malaya Alfa; Abdul Fattah Nasution (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
In madrasahs, Islamic Religious Education (PAI) plays an important role in character building for students. However, as digital technology advances, innovative methods of learning systems are needed to enhance character education. Using bibliometric research methods, this study aims to discover and analyze innovations in the PAI learning system methods in the digital era. This study summarizes various methods and techniques that can help cultivate Islamic character in madrasahs by using appropriate digital technology. The results show that the integration of technology in PAI learning, such as online methods, educational social media, and character-based learning applications, is highly likely to support the character formation of students in madrasahs to create students with noble character.